New Wor(l)ds - Jędrzejko, Paweł (Review of International American Studies, 2014)
Perhaps the most striking feature of the International American Studies Association is that since its inception our Organization has been invariably true to its creed. Indeed, the word international in our name is a dual attribute. On the one hand, the Association’s members are a community of scholars representing all inhabited continents of the world. On the other, the Studies carried out by IASA’s academic community address questions transgressing geographical thresholds and political borders. Multinational, multiethnic and multilcultural, our International Association, dedicated to the development of International Studies of the Americas, has developed a unique sensitivity to polyphony: the melody of multilingual narratives, the blending of diverse voices, the harmony of minds and hearts celebrating the richness of their individual cultural legacies reverberating in an open, friendly conversation. Over the years, IASA has managed to steer its course (or, more specifically, its three courses: transatlantic, transpacific and hemispheric), thereby effectively decentralizing American Studies, a discipline whose name has long been considered to be an alternative label to US Studies—or would predominantly be associated with research whose central point of reference would be the United States of America. Respecting and appreciating the unquestionable importance of the US as the donor of cultural values and a major political player in the international arena, we pay equally careful attention to the cultures of Canada, Mexico, Argentina, Brazil, the Carribean, Polynesia and other regions of the dual Continent. We re-visit its cultures paying attention to the entire compass of musical tones, which, sometimes, become audible only when listened to from a distance. Methodologically, we have done away with the concept of the center, replacing it with the concept of a constantly shifting perspective: therefore we seem to find it easier to watch out for the inertia of the margin. Having deconstructed the binary opposition, in our studies we systematically empower both the the ‘former margin’ and the ‘former center’—and we have been doing so without preference, without prejudice. And since ‘words’ have always-already been responsible for our conceptualization(s) of ‘worlds’, we have resolved to systematically energize a variety of concurrent quests for ‘new words’ which would then enter into dynamic relations with the ‘old ones’. Listening and learning, we constantly re-visit the once (seemingly) ‘familiar’ Americas, appreciating their inexhaustible potential of meaning: pulsing with life, the Americas refuse to be frozen in the frame of one language, one methodology or one perspective. And so do our International American Studies. The present issue, guest edited by our generous friends and colleagues—Agnieszka Woźniakowska from the University of Silesia in Katowice and Anna Łakowicz-Dopiera representing the University of Szczecin—testifies to the efficiency of IASA’s intellectual practice. Paweł Jędrzejko RIAS Associate Editor